SME’S PARTICIPATION IN REALISATION OF PROJECTS UNDER SELECTED ACTIONS OF SECTORAL OPERATIONAL PROGRAM ‘INCREASE OF ENTERPRISES’ COMPETITIVENESS’, IN RURAL AREAS OF NTS 2, 2004–2006 - Joanna Rakowska (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents results of the analysis of the number and value of projects carried out by small and medium enterprises under Sectoral Operational Program Increase of Enterprise Competitiveness. The results show that SMEs were active in carrying out analyzed projects both in urban and rural areas. However, SMEs in rural areas realized project only within actions 2.1, 2.2, 2.3 and 2.4. The number of these projects carried out in urban areas was nearly four times larger than those in rural areas. On the other hand, the projects carried out in rural areas were of a higher average value, which may be a good indication for the future actions aiming at intensification of multifunctional development of rural areas.